Os mapas nos livros didáticos de geografia e de ciências humanas e sociais aplicadas no ensino médio: currículo e construção do pensamento geográfico - Cavallini, Gabriel Martins (2022)
Geography is, historically, an important curricular component of Brazilian basic education. Therefore, in the field of Geography Teaching, we have sought to understand which methodologies and languages most contribute to the teaching-learning process of Geography. In addition, the reality of Brazilian public schools is very complex, given the social and infrastructure inequalities of the federation units. However, there is a material of almost universal access, the textbook, thus transforming it into a basic instrument of the educational system. Considering these elements, the objective of the present investigation is to analyze the cartographic language present in the Geography and Social and Applied Human Sciences textbooks of High School approved in the PNLD 2015, 2018 and 2021, reflecting on the influence of curriculum documents on these materials and the contribution of this language for the construction of geographic thought. In this sense, the investigation was structured from a documentary analysis of the reference resumes, especially the National Curricular Parameters (PCN) and the National Curricular Common Base (BNCC), as well as textbooks approved in the PNLDs 2015, 2018 and 2021. Among the results obtained through document analysis, it was found that the cartographic language is used recurrently only as an instrument for locating phenomena, making it difficult for teachers and students to weave more complex analyzes about phenomena and geographical situations. This factor shows that, in relation to the use of cartographic language for the teaching-learning process of Geography, in the context of High School, it has not been used in order to contribute to the construction of a geographical way of thinking by students.